Development of Diagnostic Instruments for Critical Thinking Skills of Students in Physics Learning on Socio-Scientific Issues (SSI) - Wulandari, Dewi Tri; Diani , Rahma; Noperi, Hendri (CV. Tripe Konsultan, 2025)
This study aimed to develop and test the feasibility of a diagnostic instrument for assessing students' critical thinking skills on socio-scientific issues (SSI) in physics education with the topic of global warming. This objective is motivated by the lack of valid, reliable, and contextually appropriate assessment instruments based on Socio-Scientific Issues (SSI) in physics education at the secondary school level, amid the low critical thinking competencies of Indonesian students as indicated by the 2018 PISA survey, and the need for an SSI approach as an effective strategy. The research method employs a research and development (R&D) design using the ADDIE model. The instrument was developed in the form of 20 essay questions based on SSI contexts and its validity was reviewed by experts and tested on 75 students from two high schools in rural and urban areas. Data were analyzed using Rasch modeling with the assistance of WINSTEPS software. Expert validation results showed that the instrument was categorized as “Highly Suitable.” Rasch model analysis confirmed the instrument's unidimensionality (raw variance explained by observed measures: 30.9%). The analysis results showed that all items were deemed fit (Outfit MNSQ: 0.78–1.28; ZSTD:–1.51 to 1.81; and PTMEA Corr: 0.26–0.68). The instrument's reliability is high, with a Cronbach's alpha of 0.81, person reliability of 0.80, and item reliability of 0.91, using a structurally valid rating scale. However, significant DIF based on gender and region was found, indicating the need for further revision to ensure measurement fairness. This instrument is deemed valid and reliable for use as a diagnostic tool for critical thinking skills in SSI-based physics learning.